Significant economic impacts due to COVID-19 and falling remittances in Myanmar - Diao, Xinshen; Wang, Michael (International Food Policy Research Institute, 2020)
The COVID-19 pandemic and government lockdown in Myanmar have led to falling exports and lost revenue from tourism and international remittances, hitting the economy hard. In a new series of policy notes, we examine the economic impacts of the pandemic and restrictive measures to mitigate the health crisis, and offer policy recommendations to address declining incomes and other impacts. Our analysis shows a major short-term economic contraction as a result of the two-week lockdown in April — a 41% decline in GDP along with similar declines in most nonagricultural sectors in comparison to the same period without a pandemic. This is not surprising, as Myanmar’s economy is deeply integrated into a complex supply network both domestically and internationally, and policies affecting certain industries have ripple effects on other sectors through supply and demand linkages. In addition, approximately 4 million Myanmar migrants work internationally, and their lost income due to lockdowns in neighboring countries is expected to impose ongoing significant burdens on low-income households that receive remittances.